Dasar Hukum perjanjian menurut perspektif Hukum Islam dan kedudukannya dalam tata Hukum Indonesia - Mulia, Wine Antika (Maliki Interdisciplinary Journal, 2024)
The law of engagement is a very important law, because its application is closely related to human activities, especially society in Indonesia. Engagement law has its own position in the Indonesian legal system. This research was conducted on June 5 2023. The method used was a literature review because the sources taken were journals, books or previous articles. The results of this research show that the basic source of contract law comes from 2 postulates, namely postulates which are in the text and which are not in the text. The basic source of the law of engagement itself is actually stated in the Qur’an. This states that the law of engagement is also regulated in this way in the Islamic religion. In the enactment of legislation regarding the law of engagement, it is also regulated from the perspective of Islamic law, as evidenced by the existence of articles that regulate this matter.